2022-RA-1608-ESGO Clinical implications of genomic intratumoural heterogeneity in high grade serous ovarian cancer. (20th October 2022) - Cunnea, Paula; Christie, Elizabeth L; Curry, Ed; Kwok, Chun-Hei; Pandey, Ahwan; Nixon, Katherine; Ploski, Jennifer; Krell, Jonathan; McNeish, Iain; Bowtell, David D; Fotopoulou, Christina
Abstract : Introduction/Background: High-grade serous ovarian cancer (HGSOC) is typified by extensive genomic instability and intra-tumoural heterogeneity (ITH). Most patients relapse and eventually acquire resistance to platinum- or PARP inhibitor-based therapy. Diverse mechanisms leading to therapy resistance and a lack of predictive biomarkers means that matching the best treatment options to patients is difficult. This study aims to describe the extent of spatial and temporal ITH in advanced stage HGSOC at presentation and relapse and its implications for patient management. Methodology: Patients (n=49) undergoing maximal-effort upfront-debulking surgery for advanced HGSOC had a tumour mapping of their tumour dissemination. Tumour biopsies were collected (range 4–15) from patients, and also at time of relapse (n=10 patients). DNA was extracted from tumours (5 per patient, n=49 patients plus paired relapse samples) and Illumina Human OmniExpress genotyping performed. Allele-specific copy number (CN) was quantified using ASCAT. CN signature exposures were determined for all samples. Homologous recombination (HR) scores were estimated using a scarHRD algorithm, applying a cut-off >42 for HR-deficient. Results: Extensive genomic variations in CN signature exposures for different patients' tumours were observed, including between matched primary and relapse tumours. Increased CN signature exposure scores for Signatures 2 (p=0.00017), 4 (p=0.0029) and 6 (p=0.001) correlated with poor outcome in platinum-resistant/refractory patients, increased Signature 3 correlated with favourable outcome (p=0.00018) for platinum-sensitive and no-relapse patients. Variations in HR scores were observed across the cohort with one fifth of patients presenting with a mixed HR score profile across their tumour deposits, demonstrating both HR-deficient and HR-proficient tumours within patients. Conclusion: Extensive CN variations in CN signature scores and mixed HR-deficiency/proficiency scores indicates that a single tumour biopsy does not accurately depict disseminated HGSOC biology, and therefore should not be used as the basis to derive biomarker profiles for prediction of patient treatment responses or outcomes.